2011
DOI: 10.1128/aac.01435-10
|View full text |Cite
|
Sign up to set email alerts
|

A Single Polymorphism in HIV-1 Subtype C SP1 Is Sufficient To Confer Natural Resistance to the Maturation Inhibitor Bevirimat

Abstract: 3-O-(3,3-Dimethylsuccinyl) betulinic acid (DSB), also known as PA-457, bevirimat (BVM), or MPC-4326, is a novel HIV-1 maturation inhibitor. Unlike protease inhibitors, BVM blocks the cleavage of the Gag capsid precursor (CA-SP1) to mature capsid (CA) protein, resulting in the release of immature, noninfectious viral particles. Despite the novel mechanism of action and initial progress made in small-scale clinical trials, further development of bevirimat has encountered unexpected challenges, because patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…For example, BMS-955176 retains activity toward variants with substitutions at Gag V370 by alanine or methionine (1.4- and 1.5-fold, respectively), and V362I (2.4-fold), as compared to 54-, 177- and 7.2-fold losses of sensitivity by BVM, respectively. In addition, BMS-955176 retains activity toward virus with V370A/ΔT371 and ΔV370 substitutions, both minor polymorphs in subtype B, but characteristic of subtype C isolates[24] (FCs of 3.5 and 6.8-fold, respectively). By comparison, BVM is >100-fold less active toward both V370A/ΔT371 and ΔV370-containing viruses.…”
Section: Resultsmentioning
confidence: 99%
“…For example, BMS-955176 retains activity toward variants with substitutions at Gag V370 by alanine or methionine (1.4- and 1.5-fold, respectively), and V362I (2.4-fold), as compared to 54-, 177- and 7.2-fold losses of sensitivity by BVM, respectively. In addition, BMS-955176 retains activity toward virus with V370A/ΔT371 and ΔV370 substitutions, both minor polymorphs in subtype B, but characteristic of subtype C isolates[24] (FCs of 3.5 and 6.8-fold, respectively). By comparison, BVM is >100-fold less active toward both V370A/ΔT371 and ΔV370-containing viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Marcelin et al (9) concluded that "HIV-1 subtype and baseline integrase polymorphisms do not influence the virologic response to RAL," whereas Armenia et al (8) concluded that "among all integrase polymorphisms, only T122I and S119P were associated with poorer virologic response to raltegravir either at 24 or 48 weeks during treatment." Overall, these studies indicate that the effect of polymorphisms on response and resistance in the INI class is not as clear as has been observed for bevirimat (2) and suggest that additional investigation may be needed. Dolutegravir (DTG; S/GSK1349572) is being developed for INI-naive patients as a once-daily, unboosted, HIV INI.…”
mentioning
confidence: 86%
“…Prevalent polymorphisms can affect the antiviral activity of some HIV antiretrovirals, as has been shown recently for the maturation inhibitor bevirimat (2) and historically for nonnucleoside reverse transcriptase inhibitors in HIV-2 infection. Thus, an examination of the effects of polymorphic sites of the IN gene on susceptibility to integrase inhibitors (INIs) is important.…”
mentioning
confidence: 99%
“…The examination of patient-derived virus revealed that BMV resistance was linked to naturally occurring polymorphisms within SP1 downstream of CA-SP1 cleavage site, in the “QVT motif” comprising SP1 residues 6, 7 and 8 [91, 92]. In vitro assays confirmed that SP1 polymorphisms, particularly SP1 V7A, reduced sensitivity of HIV-1 to BMV [88, 93]. This lack of response in a significant percentage of treated patients promoted the development of BMV analogs.…”
Section: Small Molecules and Peptides Capsid Inhibitorsmentioning
confidence: 99%